A CsPbX3 perovskite nanocrystal and preparation method thereof
The in-situ synthesis of CsPbX3 perovskite nanocrystals through gamma radiation treatment solves the problems of uneven nucleation, poor reproducibility and large energy loss in the existing methods, and achieves efficient and environmentally friendly nanocrystal preparation, with high fluorescence quantum efficiency and good stability, and is suitable for LED and solar cell devices.
Patent Information
- Application Number
- CN202310620331.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-25
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-05-25
AI Technical Summary
The existing CsPbX3 perovskite nanocrystal synthesis methods have problems such as uneven crystal nucleation, poor reproducibility and large energy loss. The traditional method is not environmentally friendly at high temperatures, and the introduction of polar solvents will destroy the stability of the nanocrystals.
CsPbX3 perovskite nanocrystals were synthesized in situ by gamma-ray radiation treatment. By placing cesium salt and lead salt precursor solutions, mixing organic halogenated hydrocarbons and organic ligands, and undergoing gamma-ray radiation treatment, a crude perovskite nanocrystal dispersion was obtained, and CsPbX3 perovskite nanocrystals were obtained through purification treatment.
A high reproducibility, simple and green preparation method of CsPbX3 perovskite nanocrystals is realized. The prepared nanocrystals have uniform size, single morphology, good dispersion and crystallinity, and the fluorescence quantum efficiency is close to 100%, which is suitable for LED and solar cell devices.
Smart Images

Figure CN116622372B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material science and technology, and in particular to a CsPbX3 perovskite nanocrystal and a preparation method thereof. Background Art
[0002] CsPbX3 (X is I, Br or Cl) perovskite nanocrystals have the advantages of high fluorescence quantum yield, tunable spectrum (410-700nm), good defect tolerance, etc., and have been widely used in laser, sensor, LED display, solar cell and other fields. Based on the above advantages and good application potential, the synthesis of CsPbX3 perovskite nanocrystals has attracted widespread attention.
[0003] At present, there are two main methods for synthesizing CsPbX3 perovskite nanocrystals: hot injection method and ligand-assisted reprecipitation method. The hot injection method mainly uses a high-temperature resistant solvent to dissolve Cs2CO3 and PbX2 (X is I, Br or Cl) as precursors under the protection of inert gas, and then quickly injects one precursor solution (Cs-OA) into another precursor solution (PbX2), and then quickly cools it with an ice water bath to stop the reaction; the nanocrystals obtained by this method are relatively uniform in size, but the strict dehydration operation and inert atmosphere limit the possibility of synthesizing a large number of nanocrystals, and the high-temperature heating (>160℃) operation is also contrary to the current "dual carbon" emission reduction and energy conservation goals. The ligand-assisted reprecipitation method is to first dissolve PbX2 and CsX (X is I, Br or Cl) in an organic solvent to form a ternary salt precursor solution, and then quickly inject it into a low-polarity solvent such as toluene and n-hexane for supersaturated crystallization; this method can prepare CsPbX3 perovskite nanocrystals without a nitrogen atmosphere, but the introduction of polar solvents will destroy the stability of CsPbX3 perovskite nanocrystals, reduce the fluorescence quantum yield, and even make it impossible to prepare CsPbX3 perovskite nanocrystals with large lattice spacing.
[0004] In addition, since the crystallization reaction process is extremely rapid (1-3 seconds), the injection time requirement for the above reaction is extremely demanding. When the experiment involves large-scale synthesis (for example, reaching the liter (L) level), the injection time is often inconsistent with the region, resulting in excessive local concentration differences, which leads to uneven crystal nucleation and poor product reproducibility. Therefore, it is of great significance to develop a highly reproducible, simple, and green preparation method for the synthesis of CsPbX3 perovskite nanocrystals.
[0005] The above contents are only used to assist in understanding the technical solution of the invention and do not constitute an admission that the above contents are prior art. Summary of the invention
[0006] The main purpose of the present invention is to propose a highly reproducible, simple and green method for preparing CsPbX3 perovskite nanocrystals, aiming to solve the above technical problems.
[0007] To achieve the above objectives, the present invention provides a method for preparing CsPbX3 perovskite nanocrystals, which uses gamma-ray radiation treatment to in-situ synthesize CsPbX3 perovskite nanocrystals.
[0008] In one embodiment, the specific steps of in-situ synthesis of CsPbX3 perovskite nanocrystals by γ-ray radiation treatment include:
[0009] S1: preparing a cesium salt precursor solution and a lead salt precursor solution;
[0010] S2: mixing the cesium salt precursor solution, the lead salt precursor solution, the organic halogenated hydrocarbon and the organic ligand I, and stirring them evenly to obtain a ternary salt precursor solution;
[0011] S3: Under stirring conditions, irradiating the ternary salt precursor solution under γ-ray radiation, wherein the total absorbed dose of γ-ray irradiation during the irradiation treatment is 1-12 kGy, to obtain a coarse dispersion of perovskite nanocrystals;
[0012] S4: purifying the coarse dispersion of perovskite nanocrystals to obtain the CsPbX3 perovskite nanocrystals, where X is at least one of Cl, Br, and I.
[0013] In one embodiment, in S1, the step of preparing the cesium salt precursor solution includes: uniformly mixing the cesium salt, the organic ligand II and the organic solvent in a preset ratio to obtain the cesium salt precursor solution; and / or,
[0014] The step of preparing the lead salt precursor solution includes: uniformly mixing the lead salt, the organic ligand III and the organic solvent according to a preset ratio to obtain the lead salt precursor solution.
[0015] In one embodiment, the cesium salt includes at least one of cesium acetate, cesium carbonate, cesium trimethylacetate, cesium hydroxide, cesium formate hydrate, cesium sulfate, cesium stearate, and cesium chromate; and / or,
[0016] The lead salt comprises at least one of lead acetate, lead oxide, lead stearate, lead succinate and lead nitrate; and / or,
[0017] The organic halogenated hydrocarbon includes at least one of chlorobenzene, dichlorobenzene, dichloromethane, chloroform, carbon tetrachloride, benzyl chloride, dichloroethane, tetrachloroethane, trimethylsilyl chloride, bromobenzene, bromopropane, bromobutylene, trimethylsilyl bromide, iodobenzene, iodoform and trimethylsilyl iodide.
[0018] In one embodiment, the organic ligand I comprises at least one of oleic acid, stearic acid, octanoic acid, palmitic acid, linolenic acid, oleylamine, octylamine, dodecylamine, tributylamine and decylamine; and / or,
[0019] The organic ligand II comprises at least one of oleic acid, stearic acid, octanoic acid, palmitic acid, linolenic acid, oleylamine, octylamine, dodecylamine, tributylamine and decylamine; and / or,
[0020] The organic ligand III includes at least one of oleic acid, stearic acid, n-octanoic acid, palmitic acid, linolenic acid, oleylamine, n-octylamine, dodecylamine, tributylamine and decylamine.
[0021] In one embodiment, the organic solvent includes at least one of N,N-dimethylformamide, dimethyl sulfoxide and isopropanol.
[0022] In one embodiment, in the step of preparing the cesium salt precursor solution, the content ratio of the cesium salt, the organic ligand II and the organic solvent is (0.05-5) mmol: (0.1-2) ml: (10-50) ml; and / or,
[0023] In the step of preparing the lead salt precursor solution, the content ratio of the lead salt, the organic ligand III and the organic solvent is (0.05-5) mmol: (0.1-2) ml: (10-50) ml.
[0024] In one embodiment, the organic ligand I includes an organic acid ligand and an organic base ligand. In S2, the volume ratio of the cesium salt precursor solution, the lead salt precursor solution, the organic halogenated hydrocarbon, the organic acid and the organic base ligand is (0.05-2):(0.1-2):(10-40):(1-8):(0.1-0.9).
[0025] In one embodiment, the specific steps of S4 include: centrifuging the coarse dispersion of perovskite nanocrystals at a speed of not less than 9000 rpm for a centrifugal time of not less than 10 min, removing the supernatant, dispersing the precipitate after centrifugation in a non-polar solvent, and taking the supernatant after natural precipitation for 24 hours to obtain the CsPbX3 perovskite nanocrystals.
[0026] The present invention also provides a CsPbX3 perovskite nanocrystal, which is prepared by the preparation method as described above.
[0027] The technical solution of the present invention solves the problems of uneven crystal nucleation, poor reproducibility and large energy loss in the existing synthesis method by using γ-ray radiation treatment to synthesize CsPbX3 perovskite nanocrystals in situ. In the technical solution of the present invention, high-energy γ-rays promote the in-situ crystallization of the reaction raw materials to synthesize CsPbX3 perovskite nanocrystals, avoiding uneven nucleation caused by local concentration differences, allowing the synthesis of large quantities of CsPbX3 perovskite nanocrystals; the preparation of the CsPbX3 perovskite nanocrystals of the present invention is carried out at room temperature and in air throughout the process, which is simple to operate and environmentally friendly. The preparation method of the present invention can prepare CsPbX3 perovskite nanocrystals with adjustable and uniform size, single morphology, good dispersibility and good crystallinity. The prepared CsPbX3 perovskite nanocrystals have good stability and nearly 100% fluorescence quantum efficiency, and can be applied to the field of LED and solar cell devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0029] Figure 1 is the X-ray diffraction spectrum (XRD) of the CsPbBr3 nanocrystals prepared in Example 1 and Example 2 of the present invention;
[0030] Figure 2 It is a characterization diagram of the ultraviolet-visible light absorption spectrum, fluorescence spectrum and photoluminescence quantum yield of the CsPbBr3 nanocrystals prepared in Examples 1 and 2 of the present invention;
[0031] Figure 3 is a transmission electron microscope (TEM) image of CsPbBr3 nanocrystals prepared in Example 1 and Example 2 of the present invention;
[0032] Figure 4 It is a size statistical diagram of CsPbBr3 nanocrystals prepared in Example 1 and Example 2 of the present invention.
[0033] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The raw materials and equipment used herein, unless otherwise specified, are commonly used in the art; the methods used herein, unless otherwise specified, are conventional methods in the art.
[0036] In this article, "include", "comprise", "contain", "contain", "have" or other variations are intended to cover non-closed inclusions, and no distinction is made between these terms. The term "include" means that other steps and ingredients that do not affect the final result can be added. The term "include" also includes the terms "consisting of..." and "consisting essentially of..." The composition and method / process of the present invention include, consist of, and consist essentially of the necessary elements and restrictions described herein and any additional or optional ingredients, components, steps or restrictions described herein. If there are descriptions involving "first", "second", etc. in this article, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first" and "second" can explicitly or implicitly include at least one of the features. In addition, if the meaning of "and / or" appears in this article is to include three parallel schemes, taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0037] All numerical values or expressions related to component amounts, process conditions, etc. used in this article should be understood to be modified by "about" in all cases. All ranges related to the same component or property include endpoints, which can be independently combined. Because these ranges are continuous, they are included in each numerical value between the minimum and maximum values. It should also be understood that any numerical range quoted herein is expected to include all sub-ranges within the range. "Parts by weight" or "parts by weight" used herein are interchangeable, and the parts by weight can be any fixed weight (such as 1mg, 1g, 2g, 5g, or 1kg, etc.) expressed in milligrams, grams, or kilograms. For example, a composition consisting of 1 part by weight of component a and 9 parts by weight of component b can be 1 gram of component a+9 grams of component b, or it can be a composition consisting of 10 grams of component a+90 grams of component b, etc.
[0038] The invention provides a method for preparing CsPbX3 perovskite nanocrystals.
[0039] In an embodiment of the present invention, the method for preparing CsPbX3 perovskite nanocrystals synthesizes CsPbX3 perovskite nanocrystals in situ by using γ-ray radiation treatment.
[0040] The specific steps of in-situ synthesis of CsPbX3 perovskite nanocrystals by γ-ray radiation treatment include:
[0041] S1: preparing a cesium salt precursor solution and a lead salt precursor solution.
[0042] S2: Mixing the cesium salt precursor solution, the lead salt precursor solution, the organic halogenated hydrocarbon and the organic ligand I, and stirring them evenly to obtain a ternary salt precursor solution; the organic ligand I has 8-24 carbon atoms to facilitate controlling the further growth of the crystal in the subsequent preparation steps.
[0043] S3: Under stirring conditions, irradiating the ternary salt precursor solution under γ-ray radiation to obtain a coarse dispersion of perovskite nanocrystals.
[0044] S4: purifying the coarse dispersion of perovskite nanocrystals to obtain the CsPbX3 perovskite nanocrystals, where X is at least one of Cl, Br, and I.
[0045] In one embodiment, in S3, the total absorbed dose of the gamma ray irradiation in the irradiation treatment is 1-12 kGy. If the absorbed dose is too low, it will affect the uniform growth of the crystal, and if the absorbed dose is too high, it will damage the product.
[0046] In one embodiment, the organic halogenated hydrocarbon includes one or more of chlorobenzene, dichlorobenzene, dichloromethane, chloroform, carbon tetrachloride, benzyl chloride, dichloroethane, tetrachloroethane, trimethylsilyl chloride, bromobenzene, bromopropane, bromobutyl, trimethylsilyl bromide, iodobenzene, iodoform and trimethylsilyl iodide.
[0047] In one embodiment, the organic ligand I is an organic acid ligand and / or an organic base ligand, the organic acid ligand includes one or more of oleic acid, stearic acid, n-octanoic acid, palmitic acid, and linolenic acid, and the organic base includes one or more of oleylamine, n-octylamine, dodecylamine, tributylamine, and decylamine. In a specific embodiment, the organic ligand I is a combination of the organic acid ligand and the organic base ligand, preferably, the organic acid ligand is n-octanoic acid, and the organic base ligand is oleylamine.
[0048] The technical solution of the present invention solves the problems of uneven crystal nucleation, poor reproducibility and large energy loss in the existing synthesis method by first synthesizing a ternary salt precursor solution containing cesium atoms, lead atoms and halogen atoms, and then using high-energy gamma rays to drive the ternary salt precursor to crystallize and generate CsPbX3 perovskite nanocrystals. In the technical solution of the present invention, high-energy gamma rays promote the mineralization of organic halogenated hydrocarbons, and the in-situ crystallization driven by halide ions avoids the uneven nucleation caused by local concentration differences, allowing the synthesis of large quantities of CsPbX3 perovskite nanocrystals; the preparation of CsPbX3 perovskite nanocrystals of the present invention is carried out at room temperature and in air throughout the process, which is simple to operate and environmentally friendly; in addition, the raw materials selected in the technical solution of the present invention are widely available and low in cost, and the selected organic halogenated hydrocarbons are common organic solvent nanocrystals, which are highly efficient and green in atomic energy, low in cost, and practical. The preparation method of the present invention can prepare CsPbX3 perovskite nanocrystals with adjustable and uniform size, single morphology, good dispersibility and good crystallinity. The prepared CsPbX3 perovskite nanocrystals have good stability and nearly 100% fluorescence quantum efficiency, and can be applied to the field of LED and solar cell devices.
[0049] According to the preparation method of the present invention, in S1, the step of configuring the cesium salt precursor solution includes: uniformly mixing the cesium salt, the organic ligand II and the organic solvent in a preset ratio to obtain the cesium salt precursor solution, wherein the organic ligand II is mainly used to dissolve the cesium salt, and the organic solvent mainly plays a role in adjusting the concentration of the solution.
[0050] According to the preparation method of the present invention, the cesium salt does not contain atoms with strong polarity including halogen atoms to reduce the difficulty of dissolving the cesium salt as much as possible. In one embodiment, the cesium salt includes one or more of cesium acetate, cesium carbonate, cesium trimethylacetate, cesium hydroxide, cesium formate hydrate, cesium sulfate, cesium stearate, and cesium chromate.
[0051] According to the preparation method of the present invention, the organic ligand II is an organic acid and / or an organic base. In one embodiment, the organic ligand II includes one or more of oleic acid, stearic acid, octanoic acid, palmitic acid, linolenic acid, oleylamine, octylamine, dodecylamine, tributylamine and decylamine.
[0052] In one embodiment, in the step of preparing the cesium salt precursor solution, the organic solvent includes at least one of N,N-dimethylformamide, dimethyl sulfoxide and isopropanol. Of course, the organic solvent may also be other solvents that are compatible with the organic ligand II.
[0053] According to the preparation method of the present invention, in S1, the step of configuring the lead salt precursor solution includes: uniformly mixing the lead salt, the organic ligand III and the organic solvent in a preset ratio to obtain the lead salt precursor solution, wherein the organic ligand III is mainly used to dissolve the lead salt, and the organic solvent mainly plays a role in adjusting the concentration of the solution.
[0054] According to the preparation method of the present invention, the lead salt does not contain atoms with strong polarity including halogen atoms to reduce the difficulty of dissolving the lead salt as much as possible. In one embodiment, the lead salt includes one or more of lead acetate, lead oxide, lead stearate, lead succinate and lead nitrate.
[0055] According to the preparation method of the present invention, the organic ligand III is an organic acid and / or an organic base. In one embodiment, the organic ligand III includes one or more of oleic acid, stearic acid, octanoic acid, palmitic acid, linolenic acid, oleylamine, octylamine, dodecylamine, tributylamine and decylamine.
[0056] In one embodiment, in the step of preparing the lead salt precursor solution, the organic solvent includes one or more of N,N-dimethylformamide, dimethyl sulfoxide and isopropanol. Of course, the organic solvent can also be other solvents that are compatible with the organic ligand III.
[0057] According to the preparation method of the present invention, the organic ligand II and the organic ligand III may be the same or different, and the organic solvent in the step of preparing the cesium salt precursor solution and the organic solvent in the step of preparing the lead salt precursor solution may be the same or different. In one embodiment, the organic ligand II is an organic acid, the organic ligand III is an organic base, and the organic solvent in the step of preparing the cesium salt precursor solution and the organic solvent in the step of preparing the lead salt precursor solution are of the same type.
[0058] According to the preparation method of the present invention, in one embodiment, in the step of configuring the cesium salt precursor solution, the content ratio of the cesium salt, the organic ligand II and the organic solvent is (0.05-5) mmol: (0.1-2) ml: (10-50) ml, preferably, the organic ligand II is oleic acid, and the mixing ratio of the cesium salt, the oleic acid and the organic solvent is 2 mmol: 6 mL: 20 mL.
[0059] In the step of preparing the lead salt precursor solution, the content ratio of the lead salt, the organic ligand III and the organic solvent is (0.05-5) mmol: (0.1-2) ml: (10-50) ml. Preferably, the organic ligand III is oleylamine, and the mixing ratio of the lead salt, the oleylamine and the organic solvent is 2 mmol: 0.4 mL: 20 mL.
[0060] In S2, the organic ligand I includes the organic acid ligand and the organic base ligand, and the volume ratio of the cesium salt precursor solution, the lead salt precursor solution, the organic halogenated hydrocarbon, the organic acid and the organic base is (0.05-2):(0.1-2):(10-40):(1-8):(0.1-0.9). Preferably, the volume ratio of the cesium salt precursor solution, the lead salt precursor solution, the organic halogenated hydrocarbon, the organic acid and the organic base is 0.2:0.5:20:4:0.5.
[0061] According to the preparation method of the present invention, in one embodiment, the specific step of S4 includes: centrifuging the coarse dispersion of perovskite nanocrystals at a speed of not less than 9000 rpm for a centrifugal time of not less than 10 min, removing the supernatant, dispersing the precipitate after centrifugation in a non-polar solvent, and taking the supernatant after natural precipitation for 24 hours to obtain the CsPbX3 perovskite nanocrystals.
[0062] The present invention also provides a CsPbX3 perovskite nanocrystal, which is prepared by the above-mentioned preparation method of the present invention. The CsPbX3 perovskite nanocrystal of the present invention has uniform size, single morphology, good dispersibility and good crystallinity, good stability and nearly 100% fluorescence quantum efficiency, and can be applied to the field of LED and solar cell devices.
[0063] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific embodiments. The embodiments are only preferred implementation modes of the present invention and are not limitations of the present invention.
[0064] Example 1
[0065] S1: Weigh 384 mg of cesium acetate, 6 mL of oleic acid and 20 mL of N, N-dimethylformamide, add them to a sample bottle, stir and dissolve to obtain a clear and transparent Cs-OA solution (cesium salt precursor solution); and weigh 758.6 mg of lead acetate trihydrate, 0.4 mL of oleylamine and 20 mL of N, N-dimethylformamide, add them to a sample bottle, stir and dissolve to obtain a clear and transparent Pb-OAm solution (lead salt precursor solution).
[0066] S2: 20 mL of bromobenzene was added to a single-necked flask, and then 0.5 mL of Cs-OA solution and 0.5 mL of Pb-OAm solution were added to the single-necked flask, and then 4 mL of oleic acid and 0.5 mL of oleylamine ligand were added, and a clear and transparent ternary salt precursor solution was obtained after stirring evenly.
[0067] S3: Under stirring conditions, the ternary salt precursor solution is irradiated with 60Co-γ rays, and after the irradiation, a coarse dispersion of CsPbBr3 perovskite nanocrystals is obtained.
[0068] S4: The CsPbBr3 perovskite nanocrystal coarse dispersion is centrifuged at a speed of 9000 rpm for 10 min, the upper clear liquid is discarded, the precipitated material after centrifugation is dispersed in toluene for ultrasonic dispersion to form a nanocrystal dispersion, and the upper clear liquid is taken after natural precipitation for 24 hours to obtain a high-purity CsPbBr3 perovskite nanocrystal dispersion.
[0069] Example 2
[0070] Based on Example 1, the only difference is that the oleic acid in step S3 is replaced by n-octanoic acid.
[0071] Experimental test analysis
[0072] (1) X-ray diffraction characterization was performed on the CsPbBr3 perovskite nanocrystals prepared in the above-mentioned Examples 1 and 2. The CsPbBr3 perovskite nanocrystals were drop-coated on a silicon wafer and scanned immediately after the solvent dried. The test results can be found in Figure 1 , Figure 1 Figure a and Figure b are test images of CsPbBr3 perovskite nanocrystals prepared in Example 1 and Example 2, respectively.
[0073] analyze Figure 1It can be obtained that the X-ray diffraction curves of the perovskite nanocrystals prepared by oleic acid (a) or octanoic acid (b) respectively have double diffraction peak characteristics, and the diffraction peaks near 2θ=15.2° and 2θ=31° are well matched with the orthorhombic phase CsPbBr3 perovskite (crystallography database ICSD 14608 standard card), indicating that the CsPbBr3 perovskite nanocrystal product prepared by the present invention is pure, wherein the broadening of the characteristic diffraction peak is due to the reduction in the crystal size of the CsPbBr3 perovskite nanocrystal.
[0074] (2) The CsPbBr3 perovskite nanocrystals prepared in Examples 1 and 2 were characterized by UV-visible absorption spectrum, fluorescence spectrum and photoluminescence quantum yield. Please refer to the test structure for details. Figure 2 . Figure 2 Figure a and Figure b are test images of CsPbBr3 perovskite nanocrystals prepared in Example 1 and Example 2, respectively.
[0075] analyze Figure 2 It can be obtained that the absorption spectrum curves of the perovskite nanocrystal liquid prepared by oleic acid (a) and octanoic acid (b) respectively have absorption sidebands, which are cut off at around 500nm, which is consistent with the absorption characteristics of the perovskite nanocrystal product. The perovskite nanocrystal dispersion emits green light under 365nm ultraviolet light excitation. The perovskite nanocrystal prepared by oleic acid (a) also contains shoulder peaks at 450nm and 470nm. It may be that the particle size of the perovskite nanocrystal has a smaller distribution, and its quantum confinement effect is enhanced, resulting in a blue shift in emission, and the fluorescence quantum efficiency is 38%; in contrast, the perovskite nanocrystal prepared by octanoic acid (b) has a fluorescence emission peak at 499nm, with a small Stokes shift, and a half-peak width of less than 20nm. The narrower half-peak width means that the color is purer, and its fluorescence emission yield (PLQY) reaches 96%. This shows that the carbon chain of the organic acid used in step S3 of the present invention should not be too long. Nanocrystals synthesized using organic acids with medium-length carbon chains have few defects and high radiation recombination efficiency, and are very suitable for use as display luminescent materials.
[0076] (3) The microscopic morphology of the CsPbBr3 perovskite nanocrystals prepared in Examples 1 and 2 was tested and analyzed. Figure 3 and Figure 4 . Figure 3 Figures a and b are transmission electron microscope (TEM) images of CsPbBr3 perovskite nanocrystals prepared in Example 1 and Example 2, respectively; Figure 4 Figure a and Figure b are size statistics of CsPbBr3 perovskite nanocrystals prepared in Example 1 and Example 2, respectively.
[0077] analyze Figure 3It can be seen that the CsPbBr3 perovskite nanocrystals prepared in Example 1 and Example 2 both have a certain anisotropy, the nanocrystals prepared with oleic acid have a wider distribution, and the nanocrystals prepared with n-octanoic acid have a narrower size distribution. Figure 4 It can be obtained that the nanocrystals prepared by oleic acid have a longitudinal size of 19.8±5.3nm, a lateral size of 7.8±2.1nm, and an aspect ratio of 2.8; the nanocrystals prepared by octanoic acid have a longitudinal size of 18.6±3.5nm, a lateral size of 11.7±2.6nm, and an aspect ratio of 1.6, having a smaller aspect ratio and distribution.
[0078] The morphology of the perovskite nanocrystals prepared by the present invention is different from the cubic morphology of nanocrystals synthesized by the hot injection method. This is because the hot injection method rapidly nucleates and grows in a cubic α phase at high temperature, while the radiation method slowly grows in an orthorhombic γ phase at room temperature. However, anisotropy does not prevent the perovskite nanocrystals from having extremely high fluorescence quantum yields, indicating that the slow crystallization kinetics avoids the enrichment of defects and reduces non-radiative recombination. Based on the above test results, it can be seen that the CsPbX3 perovskite nanocrystals prepared by the preparation method of the present invention achieve efficient luminescence, uniform morphology, good crystallization and simple methods, and can be applied to fields such as LED devices.
[0079] The foregoing examples are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to claim the widest possible range that can be conceived, and the embodiments presented herein are only illustrations of selected implementations according to the combination of all possible embodiments. Therefore, it is the applicant's intention that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges within them, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.
[0080] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific embodiments. The embodiments are only preferred implementation modes of the present invention and are not limitations of the present invention.
Claims
1. A method for preparing CsPbBr3 perovskite nanocrystals, characterized in that: The in-situ synthesis of CsPbBr3 perovskite nanocrystals by gamma-ray radiation treatment comprises the following steps: S1: preparing a cesium salt precursor solution and a lead salt precursor solution; S2: Mixing the cesium salt precursor solution, the lead salt precursor solution, the organic halogenated hydrocarbon and the organic ligand I, and stirring evenly to obtain a ternary salt precursor solution, wherein the organic halogenated hydrocarbon is bromobenzene, The organic ligand I is n-octanoic acid and oleylamine; S3: Under stirring conditions, irradiating the ternary salt precursor solution under γ-ray radiation, wherein the total absorbed dose of γ-ray irradiation during the irradiation treatment is 1-12 kGy, to obtain a coarse dispersion of perovskite nanocrystals; S4: purifying the coarse dispersion of perovskite nanocrystals to obtain the CsPbBr3 perovskite nanocrystals.
2. The preparation method according to claim 1, characterized in that In S1, the step of preparing the cesium salt precursor solution includes: uniformly mixing the cesium salt, the organic ligand II and the organic solvent in a preset ratio to obtain the cesium salt precursor solution; and / or, The step of preparing the lead salt precursor solution includes: uniformly mixing the lead salt, the organic ligand III and the organic solvent according to a preset ratio to obtain the lead salt precursor solution.
3. The preparation method according to claim 2, characterized in that: The cesium salt includes at least one of cesium acetate, cesium carbonate, cesium trimethylacetate, cesium hydroxide, cesium formate hydrate, cesium sulfate, cesium stearate, and cesium chromate; and / or, The lead salt includes at least one of lead acetate, lead oxide, lead stearate, lead succinate and lead nitrate.
4. The preparation method according to claim 2, characterized in that: The organic ligand II comprises at least one of oleic acid, stearic acid, octanoic acid, palmitic acid, linolenic acid, oleylamine, octylamine, dodecylamine, tributylamine and decylamine; and / or, The organic ligand III includes at least one of oleic acid, stearic acid, n-octanoic acid, palmitic acid, linolenic acid, oleylamine, n-octylamine, dodecylamine, tributylamine and decylamine.
5. The preparation method according to claim 2, characterized in that: The organic solvent includes at least one of N,N-dimethylformamide, dimethyl sulfoxide and isopropanol.
6. The preparation method according to claim 2, characterized in that: In the step of preparing the cesium salt precursor solution, the content ratio of the cesium salt, the organic ligand II and the organic solvent is (0.05-5) mmol: (0.1-2) ml: (10-50) ml; and / or, In the step of preparing the lead salt precursor solution, the content ratio of the lead salt, the organic ligand III and the organic solvent is (0.05-5) mmol: (0.1-2) ml: (10-50) ml.
7. The preparation method according to claim 6, characterized in that: In S2, the volume ratio of the cesium salt precursor solution, the lead salt precursor solution, the organic halogenated hydrocarbon, the n-octanoic acid and the oleylamine ligand is (0.05-2):(0.1-2):(10-40):(1-8):(0.1-0.9).
8. The preparation method according to any one of claims 1 to 7, characterized in that: The specific steps of S4 include: centrifuging the coarse dispersion of the perovskite nanocrystals at a speed of not less than 9000 rpm and a centrifugal time of not less than 10 min, removing the supernatant, dispersing the precipitate after centrifugation in a non-polar solvent, and taking the supernatant after natural precipitation for 24 hours to obtain the CsPbBr3 perovskite nanocrystals.
Citation Information
Patent Citations
Preparation method of dimension-controllable CsPbX3 perovskite nanometer crystals
CN108101102A